Clinical significance of anti-Epstein–Barr virus antibodies in systemic chronic active Epstein–Barr virus disease - Nishio, Miwako; Saito, Minori; Yoshimori, Mayumi; Kumaki, Yuki; Ohashi, Ayaka; Susaki, Eri; Yonese, Ichiro; Sawada, Megumi; Arai, Ayako (Frontiers in Microbiology, 2024)
Systemic chronic active Epstein-Barr virus disease (sCAEBV) is a rare and fatal neoplasm, involving clonally proliferating Epstein-Barr virus (EBV)-infected T cells or natural killer cells. Patients with sCAEBV have abnormal titers of anti-EBV antibodies in their peripheral blood, but their significance is unknown. We retrospectively investigated titers and their relationship with the clinical features of sCAEBV using the data collected by the Japanese nationwide survey. Eighty-four patients with sCAEBV were analyzed. The anti-EBV nuclear antigen (EBNA) antibody, targeting EBNAexpressing EBV-positive cells, was found in 87.5% of children (<15 years old), 73.7% of adolescents and young adults (15-39 years old), and 100% of adults (≥40 years old). Anti-EBNA antibody titers were significantly lower and anti-VCA-IgG antibody titers significantly higher in patients with sCAEBV than those in healthy controls (p <0.0001).Patients with high anti-VCA-IgG and anti-early antigen-IgG antibody (antibodies against the viral particles) levels had significantly better 3-year overall survival rates than those with low titers, suggesting that patients with sCAEBV have a reduced immune response to EBV-infected cells.